Disclosure of positive Human Immunodeficiency Virus status to children diagnosed with the infection and on antiretroviral treatment - Muditambi, Nathaniel Nndavheleseni (My University, 2023)
Introduction and background: Disclosure of HIV status remains low in South Africa and globally. Care givers commonly delay the HIV disclosure process until the child is over 10 years of age. The World Health Organization (WHO) reports that disclosure of HIV status to infected children, as the gateway to treatment, has failed to keep pace with the increasing access to ART globally. Non-disclosure if allowed to continue can have negative ramifications for not only the affected children but the entire nation. The study, therefore, envisages determining and exploring the experiences of care givers as they disclose to individual children under their care about their HIV status. Methodology: Qualitative, explorative, and descriptive phenomenological design was utilised to respond to the objectives of this study, to describe the experiences of primary care givers regarding HIV disclosure to children living with HIV. This study was conducted in Mopani District Limpopo Province, South Africa. Sixteen care givers were included in the study. Non-probability sampling was utilised to sample the facility for inclusion and the participants in this study. Semi-structured and face-to-face interviews were conducted to collect data from participants. During data collection, the researcher used an interview guide, and the participants were audio-recorded. Data were analysed using the ATLAS.ti 9 program, according to the thematic method of analysis. Results: Care givers indicated that they have trouble initiating the HIV disclosure process for the child. Care givers also state that they disclosed HIV status to the child because of their individual reasons, they believe is the right of the child to know the truth about their condition and the treatment they are taking. Care givers expressed that HIV disclosure improves child understanding of their condition, the importance of treatment, adherence, and quality of life. Care givers state that non-disclosure of HIV status resulted in children refusing treatment, which will lead them to get sick and increases the risk of HIV transmission to others. Care givers state that they didn’t receive any training or education from healthcare providers. Conclusion: Care giver’s experience suggested that HIV disclosure is a difficult process to initiate and is aggravated by a lack of skills and support from healthcare providers on how to disclose HIV to children. However, care givers acknowledge the importance of HIV disclosure and the complication of non-HIV disclosure. More support from a health provider is required to guide care givers to initiate HIV the disclosure process at an ideal age.
Thesis (M.A. (Nursing)) -- University of Limpopo, 2023
Keywords: Immune Deficiency Virus; Antiretroval; Primary care givers; HIV-positive children; HIV (Viruses); Antiretroviral agents